The priest barracks : Dachau, 1938-1945 - Zeller, Guillaume (Ignatius Press, 2017)
At the Nazi concentration camp Dachau, three barracks out of 30 were occupied by clergy from 1938-1945. The overwhelming majority of the 2,720 men imprisoned in these barracks were Catholics including monks and seminarians from all over Europe. More than a third of the prisoners in the "priest block" died there. The story of these men which has been submerged by the overall history of the concentration camps, is told in this riveting historical account. Besides recounting moving episodes, this book sheds new light on Hitler's system of concentration camps and the intrinsic anti-Christian animus of Nazism.